The practical of precaution/isolation from the medical diagnosis in infectious disease unit - Rosely Moralez de Figueiredo; Cristiane Leite (Universidade Federal de Goias, 2006)
With the aim of analyzing the use of an infectious disease unit in a medium size general hospital, 95 patients records were examined; 72,6% of the patients were male; the average age was 41 and the average permanence in hospital was 15, 7 days. The death rate was 12,6%. The main medical diagnosis were AIDS in 52,4% and tuberculosis in 6,3% of patients. The speciality infectology was responsible for 35,8% of confinements. Regarding precautions for transmission 14,7% needed air precautions, 8,5% contact precautions, 1,1% droplets and the other 75,7% only standard precautions. A variety of criteria for confinement, not only the infectious nature of the disease, stands out in the unit; the generic term "isolation" is maintained in the records. Unification of the practical employed, education programs in service that aim at appropriation and the use of technical knowledge about precautions by the whole health team are advised.